Las competencias digitales y su aporte en la educación actual de los estudiantes universitarios - Llumitaxi Aguilar, Norelys Maciel (2020)
This project presents an analysis of digital competences and their contribution to the current education of university students. We are in an era where technology has generated repercussions in all areas of society, so that in higher education is not left behind as it has influenced everything related to the study of the current student. Firstly, a theoretical review is carried out about the definitions and characteristics of digital competencies. Those people who have been born in this era where the digital is the boom of the moment are those who are already used to being permanently connected or their facility to obtain quick information. Therefore, some characteristics, types of digital competences and their benefits are also presented. Finally, the topic of the contributions of these in the university student is approached. In this digital generation, the university must develop strategies that allow the student to develop through digital competence during his/her professional training stage. In this project, an analysis of this important issue is made and relevant information for students and society is shown.